FİBER ELEMAN YÖNTEMİ KULLANILARAK BETONARME YAPILARIN DOĞRUSAL OLMAYAN SİSMİK ANALİZİ İLE BURULMA DAVRANIŞININ İNCELENMESİ - YILMAZ, İSRA (Fırat Üniveristesi, 2022)
Bu çalışmada, 15×15 m boyutlarına sahip 24 katlı betonarme üç tip yüksek binanın (Tip-1, Tip-2, Tip-3) doğrusal olmayan sismik analizleri yapılmıştır. Perdeler, Tip-1 binasında çekirdekte, Tip-2 binasında köşelerde ve Tip-3 binasında ise dış kenarların ortalarında konumlandırılmıştır. Tüm binalarda dört farklı perde alanı seçilmiştir. Betonarme taşıyıcı elemanların kesitleri Kuvvete Dayalı Fiber Eleman Yöntemi ile modellenmiştir. Sismik analizlerde her katın döşemesi rijit diyafram kabul edilmiştir. Deprem yükü için TBDY-2018' e göre yapay olarak üretilmiş 11 adet ivme kaydı kullanılmış olup bu ivme kayıtları tüm binaların her iki doğrultusunda etki ettirilmiştir. Karşılaştırmalar, binalardaki hasar bölgesi, bina tepesinin burulma açısı, açısal hız ve açısal ivme tepkilerinin mutlak maksimumlarının maksimum ve ortalama değerleri için yapılmıştır. Kolon ve perde elemanların farklı hasar bölgelerine geçen oranları karşılaştırıldığında en az hasara sahip olan binanın Tip-2 olduğu belirlenmiştir. Aynı zamanda, burulma açısı, açısal hız ve açısal ivme tepkilerinin mutlak maksimumlarının maksimum değerleri dikkate alındığında en düşük değerleri veren bina tipinin Tip-2 olduğu görülmüştür. Sonuç olarak burulma davranışı açısından en uygun bina tipinin Tip-2 olduğu belirlenmiştir.

In this study, nonlinear seismic analyses of three type high reinforced concrete building (Type-1, Type-2, Type-3) that has 15x15m dimensions and 24 stories, are obtained. Shear walls are located in the core of the building for the Type-1, at the corners of the building for the Type-2, and in the middle of the exterior edges of the building for the Type-3. Four different shear wall areas are selected for whole building types. The cross-sections of the reinforced concrete elements are modeled by using the Force-Based Fiber Element Method. In the seismic analyses, the floor of each story is assumed as a rigid diaphragm. 11 artificial earthquake acceleration records are used according to TBDY-2018 for the earthquake loading and, are applied to both directions of each type of buildings. Comparisons are obtained for the damage area of buildings, the maximum of absolute maximum values and mean values of the torsion, angular velocity, and angular acceleration responses of the top of the building. When the rates of column and shear wall elements that have different damage areas are compared, it has been determined that the least damaged building is Type-2. At the same time, when the absolute maximum values of torsion, angular velocity, and angular acceleration responses are taken into account, it has been concluded that the building giving the lowest responses is Type-2. As a result, it has been determined that the most applicable building type with regard to torsional behavior is Type-2.
Keywords: İnşaat Mühendisliği